Quantifying Land Use/ Land Cover Dynamics in Sandran Watershed, Part of Jehlum Basin in Western Himalayas, Kashmir, India - Nandia, Adil Manzoor; Ahmed, Pervez; Kanth, T. A.; Tali, Parvaiz A. (National Geographical Journal of India, 2022)
Not available